1997
DOI: 10.1007/s000400050046
|View full text |Cite
|
Sign up to set email alerts
|

Ant litter fauna of forest, forest edges and adjacent grassland in the Atlantic rain forest region of Bahia, Brazil

Abstract: SummaryThe litter ant fauna was sampled by Winkler sacks and pitfall traps along transects running through Atlantic rain forest into an adjacent grassland. Transects ran 65 m into the forest and 45 m into the field. Ninety-seven species of ants were sampled and scored, 85 were found in the forest, 48 were found in the field and 36 were common to both habitats. There was some evidence that species richness was lowest in the field and high at the deepest point within the forest. The composition of the ant commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
12

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 22 publications
0
40
0
12
Order By: Relevance
“…Desse modo, práticas agrícolas intensivas interfeririam na composição das comunidades de formigas, e são provavelmente responsáveis por certa homogeneização da fauna dos agroecossistemas na região. Embora a diversidade de espécies geralmente diminua com a criação abrupta de uma borda (LOVEJOY et al, 1986), é provável que as bordas tenham papel duplo na composição de espécies nos ecossistemas adjacentes, funcionando como uma "zona tampão", evitando a ruptura da composição das espécies e assim a perda de diversidade no interior da floresta (MAJER et al, 1997). Além disso, podem funcionar como uma zona de transposição (fonte) de espécies da floresta adjacente para o agroecossistema, proporcionando a manutenção de inimigos naturais na cultura, que seria de suma importância no controle biológico de pragas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Desse modo, práticas agrícolas intensivas interfeririam na composição das comunidades de formigas, e são provavelmente responsáveis por certa homogeneização da fauna dos agroecossistemas na região. Embora a diversidade de espécies geralmente diminua com a criação abrupta de uma borda (LOVEJOY et al, 1986), é provável que as bordas tenham papel duplo na composição de espécies nos ecossistemas adjacentes, funcionando como uma "zona tampão", evitando a ruptura da composição das espécies e assim a perda de diversidade no interior da floresta (MAJER et al, 1997). Além disso, podem funcionar como uma zona de transposição (fonte) de espécies da floresta adjacente para o agroecossistema, proporcionando a manutenção de inimigos naturais na cultura, que seria de suma importância no controle biológico de pragas.…”
Section: Discussionunclassified
“…Esses himenópteros têm sido utilizados também como ferramentas de bioindicação para avaliar e monitorar várias situações ambientais distintas (MAJER, 1992(MAJER, , 1996MAJER et al, 1997;MAJER & DELABIE, 1999;VASCONCELOS, 1999;TEIXEIRA et al, 2005), por apresentarem ampla distribuição geográfica e abundância local, alta riqueza de espécies e por serem mais facilmente amostrados e identificados que outros organismos .…”
unclassified
“…A positive relationship between species richness and habitat complexity often is found in tropical and subtropical ant communities (Majer et al 1997, Vasconcelos & Vilhena 2006, but see Lassau & Hochuli 2004). In lowland forests with higher canopy and strong presence of epiphytes, arboreal ants largely contribute to forest richness (Vasconcelos & Vilhena 2006, Neves et al 2013).…”
Section: Species Richness and Compositionmentioning
confidence: 99%
“…Most known ant species live in the soil and in the leaf litter of tropical forests (Wall and Moore 1999;Silva and Silvestre 2004). Standardized sample design helped to increase our knowledge on the ant fauna of Brazilian biomes, in particular leaf litter ants of Atlantic Forest (see Majer et al 1997;Veiga-Ferreira et al 2005;Vargas et al 2007). Association of sampling techniques, such as Winkler's extractors and pitfall traps (Olson 1991;Bestelmeyer et al 2000), may sample 75 % of all ant species found in leaf litter, a representative sample for many ecological studies that also allows new records of species.…”
mentioning
confidence: 99%